Link Budget Analysis for 5G Communication in the Tropical Regions - Patra, Trilochan; Mitra, Swarup Kumar (Wireless Communications and Mobile Computing, 2020)
In the tropical regions, when a signal is transmitted from a transmitter to a receiver, the signal gets highly attenuated because of heavy rainfall. By using different diversity techniques, this signal attenuation is minimized. The multiple-input multiple-output (MIMO) system is an antenna diversity technique, and in this paper, this technique has been applied to the proposed communication link model designed for 5G communication in the tropical regions. Here, a proposed link budget has been set down to enhance the signal power and signal-to-noise ratio (SNR) at the receiver. In this paper, an experimental data sheet has also been adopted to achieve the desired result of the proposed link budget. In fine, a comparison of assumption values of the proposed link budget with practical values obtained from the experimental data sheet has been displayed in the result analysis part.